Digitalization of housing and communal services using the example of apartment buildings - Smirnov M.Yu.; Ziyautdinov V.S.; Voronin I.V.; Zolotareva T.A. (E3S Web of Conferences, 2020)
The possibility of digitalization of housing and communal services is mathematically considered using the example of apartment buildings. The approaches discussed in the paper can be used in the construction of new apartment complexes, as well as in the overhaul of the existing housing stock. In addition, the applied approaches can be easily adapted for use in office buildings and business centers.